Top managers' environmental values, leadership, and stakeholder engagement in promoting environmental sustainability in the restaurant industry. (May 2017) - Jang, Yoon Jung; Zheng, Tianshu; Bosselman, Robert
Highlights: A theoretical framework of restaurants' environmental sustainability was proposed. Top managers' environmental values influenced restaurants' environmental commitment. Top managers' leadership influenced restaurants' environmental commitment. Stakeholder engagement strongly influenced restaurants' environmental commitment. Restaurants' environmental performance influenced (non)financial performance. Abstract: This study examines the role of top managers' values and leadership in advancing environmental sustainability. It also investigates the effects of stakeholder engagement on restaurants' environmental sustainability and assesses the impact of related practices on restaurant performance. A web-based survey was administered to collect data from top-level restaurant managers in the United States. The sample was selected from panels recruited by a research company specializing in panel surveys. Invitation emails were sent to 2500 managers and 240 responses were returned, 218 of which were retained for final analysis (response rate: 8.7%). Structural equation modeling was used for testing hypothetical relationships among key constructs in the proposed research model: environmental values, leadership, stakeholder engagement, environmental sustainability, and restaurant performance. Findings confirmed the significant role of top management values and leadership in advancing environmental commitment. The results also demonstrated the strong impact of stakeholder engagement on restaurants' commitment to environmental sustainability. Finally, they indicated the positive influence of restaurants' environmental sustainability performance on both financial and nonfinancial performance. The study presents a theoretical framework, integrating theories or models from extant literature, and contributes to an enhanced understanding of restaurants' environmental sustainability. The findings suggest several practical implications for managers in the restaurant industry.